CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF KALAKAI (Stenochlaena palustris) LEAVES EXTRACT IN NANOSTRUCTURED LIPID CARRIER SYSTEM - Fahrina, Nurhaliza; Aris, Fadillah; Muhammad, Fauzi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
Exposure to ultraviolet light can cause damage and death of skin cells through multiple mechanisms, including the formation of free radicals that can cause hyperpigmentation, erythema, sunburn, photo-aging, and even skin cancer. Kalakai (Stenochlaena palustris) is a typical Kalimantan plant with the ability to be a high antioxidant. However, it is still very rarely utilized. Kalakai leaves contain polyphenolic groups that function as free radical antidotes, as well as flavonoid compounds that can stabilize radical compounds. Various technology-based drug delivery systems have been developed to improve therapeutic effectiveness, including nanotechnology. Nanostructured lipid carrier (NLC) is the second-generation lipid-based carrier designed to overcome the limitations of previous-generation lipid-based carriers. This system consists of a mixture of and unstructured due to their different constituent parts. This research will develop a formula for kalakai leaf extract in a nanostructured lipid carrier system using the emulsification-sonication method. Based on the data, the characteristics of kalakai leaf extract in a nanostructured lipid carrier system that meet the standards are F1 (5%) and F2 (10%). Among the three formulas, F3 showed the highest IC50 value compared to F1 and F2, which is 14,967 ± 0,240 with powerful antioxidant activity, followed by F2 with an IC50 value of 24,186 ± 1,797, and F1 with IC50 value of 65,504 ± 5,041.